Effects of different concentrations of Lactiplantibacillus plantarum and Bacillus licheniformis on silage fermentation parameter, chemical composition and microbial community of Pennisetum sinese - Chen, Qiong; Yu, Baisheng; Zhu, Yanchen; Xiong, Haoming; Guo, Yongqing; Liu, Dewu; Sun, Baoli (Frontiers in Microbiology, 2025)
The purpose of the experiment was to study the effects of different concentrations of Lactiplantibacillus plantarum (LP) and Bacillus licheniformis (BL) on the quality of Pennisetum sinese (PS) silage. The experiment consisted of seven treatment groups. The control group did not use additives, and the experimental groups were added with LP or BL of 1 × 105 CFU/g fresh weight (FW), 1 × 106 CFU/g FW and 1 × 107 CFU/g FW, respectively. The nutritional value of Pennisetum sinese silage was comprehensively evaluated using CNCPS 6.5 system and 16sDNA sequencing technology. The results showed that the ammonia nitrogen content and pH of each experimental group were significantly lower than those of the control group (p < 0.05). The starch content gradually decreased and the water-soluble carbohydrate (WSC) content increased in both LP and BL groups with the increase of addition concentration. The LP7 group could significantly increase the true protein content in protein (p < 0.05), and CP in BL groups decreased gradually with the increase of concentration. Compared with the control group, the content of neutral detergent fiber (NDF) and acid detergent fiber (ADF) was significantly lower in LP7 group (p < 0.05) and the ADF content was significantly lower in BL5 group (p < 0.05). In addition, LP and BL were able to change the proportion of each component in CNCPS system for Pennisetum sinese silage. The use of LP and BL can reduce the relative abundance of harmful microorganisms in silage such as Sediminibacterium and Nitrospira, and significantly change the microbial community structure in silage (p < 0.05). In conclusion, LP and BL have significant effects on silage quality and nutritional value. The nutritional value of Pennisetum sinese in LP groups showed a dose-dependent effect, and adding 1 × 107 CFU/g LP have the best effect in silage. The best effect was achieved by adding 1 × 105 CFU/g BL in BL groups, and the effect of LP7 group was better than that of BL5 group.